Macrophage metabolic reprogramming during chronic lung disease - Ogger, Patricia P. (Mucosal Immunol, 2020)
Airway macrophages (AMs) play key roles in the maintenance of lung immune tolerance. Tissue tailored, highly specialised and strategically positioned, AMs are critical sentinels of lung homoeostasis. In the last decade, there has been a revolution in our understanding of how metabolism underlies key macrophage functions. While these initial observations were made during steady state or using in vitro polarised macrophages, recent studies have indicated that during many chronic lung diseases (CLDs), AMs adapt their metabolic profile to fit their local niche. By generating reactive oxygen species (ROS) for pathogen defence, utilising aerobic glycolysis to rapidly generate cytokines, and employing mitochondrial respiration to fuel inflammatory responses, AMs utilise metabolic reprogramming for host defence, although these changes may also support chronic pathology. ﻿This review focuses on how metabolic alterations underlie AM phenotype and function during CLDs. Particular emphasis is given to how our new understanding of AM metabolic plasticity may be exploited to develop AM-focused therapies.